Multi-joint Compensatory Effects of Unilateral Total Knee Arthroplasty during High-Demand Tasks - Gaffney, Brecca M. (Ann Biomed Eng, 2015)
Patients with total knee arthroplasty (TKA) demonstrate quadriceps weakness and functional limitations one year after surgery during daily tasks such as walking and stair climbing. Most biomechanical analyses of patients after TKA focus on quadriceps function and rarely investigate other lower-extremity muscles or high-demand ambulatory activities of daily living. The purpose of this investigation was to quantify lower-extremity muscle forces in patients with unilateral TKA during high-demand tasks of pivoting and descending stairs. Five patients with unilateral TKA and five age and sex-matched controls performed three bilateral high-demand tasks: 1) step down from an 8-inch platform, 2) inside pivot: 90° direction change toward planted limb, and 3) outside pivot: 90° direction change away from planted limb. Subject-specific musculoskeletal simulations were created in OpenSim to determine joint angles, moments, and lower-extremity muscle forces. The results indicate that patients with TKA adopt compensatory strategies at both the hip and knee. Patients with TKA demonstrated increased hip external rotation, decreased knee flexion, decreased quadriceps force, and decreased hip abductor force in all three tasks. These strategies are likely a result of quadriceps avoidance, which may stem from instability after TKA or a habitual strategy developed during the late stages of osteoarthritis.